COMMUNICATION OF DEAF PEOPLE BASED ON THE ORAL METHOD (Heritage, 2021)
Throughout history, the phenomenon of hearing impairment has been the subject of interest of altruists, philosophers, doctors, priests, teachers and pedagogues. Today, this phenomenon is approached from a multidisciplinary aspect: medical, special education, sociological, pedagogical, psychological, linguistic, cultural and technological, all off which have the communication of deaf and hard of hearing people as a thing in common. Different approaches in building communication systems for deaf have led to three basic groups of methods: nonverbal, oral and combined. This paper will present an analysis of the development and application of the oral method, which at a certain point in time played a significant role in the process of education and rehabilitation of the deaf, with special emphasis on methods of demutation, ie speech and language construction in the deaf.
Keywords: deafness; deaf; communication; oral methods